Post a New Question

Find the limit

posted by on .

Compute lim f(2+h)-f(2)
h->0 ---------
h

  • Find the limit - ,

    did you mean
    Compute lim( f(2+h)-f(2) )/h as h ---> 0 ?

    If so, then this has the appearance of attempting to find the derivative of f(x) = x by First Principles when x = 2

    Short way is to know that
    f ' (x) = 1 , and so the result would be 1

    long way:
    lim( f(2+h)-f(2) )/h as h ---> 0
    = lim ( x + h - x)/h as h --> 0
    = lim h/h
    = 1

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question